Mitigating Workload Imbalance in Hazardous Situations through Mobile Sink Coordination - Arati, Arati; Patil , Manoj (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper addresses the critical issue of workload imbalance in hazardous situations, where uneven distribution of tasks can impede effective response efforts. The proposed solution revolves around the innovative concept of mobile sink coordination, leveraging adaptable and agile data collection points. The study emphasizes the importance of real-time decision-making, resource optimization, and collaborative efforts to ensure a well-coordinated response. The overview establishes the significance of workload balance in hazardous events, introducing mobile sink coordination as a promising solution. Mobile sinks, strategically deployed, dynamically distribute tasks based on evolving demands, thereby enhancing response efficiency. The study unfolds by exploring the technical aspects of implementing mobile sink coordination, including communication protocols, route planning, and resource allocation algorithms. By integrating mobile sink coordination into hazard response strategies, the study envisions a future where data-driven decisions are bolstered by dynamic task distribution. Through empirical analysis and simulations, the paper aims to demonstrate the tangible benefits of this approach in mitigating workload imbalances, enhancing the resilience of response teams, and contributing to safer and more efficient outcomes in hazardous situations. Ultimately, the study aspires to transform the way tasks are allocated and executed, advancing hazard mitigation and response strategies for a safer and more effective future.